Analisa Konveksi Paksa (Pemaksaan Udara Masuk) pada Proses Pembakaran Briket Ampas Sagu - Haurissa, Jusuf; Riupassa, Helen (Jurusan Teknik Mesin, Fakultas Teknik, Universitas Brawijaya, 2020)
In previous studies, the initial process of burning briquettes still takes a long time, i.e. app 15-20 minutes. In normal briquette burning, a flame comes out from the briquette hole surface. The purpose of this research is to find a solution to accelerate the burning process and then the solution to use this process easily. The main objective of this research is to examine the amount of heat generated from the briquettes burning process with the number of holes as much as 10, 12, and 14, and to measure the time of initial briquette burning until the first time the flame came out on the briquettes surface. The basic ingredients of briquettes used in this study were sago waste. The tools used are a moisture meter to measure the water content, an infrared thermometer, a temperature measuring instrument, a Stopwatch to measure time, a digital anemometer to measure the airflow speed. From this study, the results obtained indicate that the combustion process in a forced air convection conditions, resulting in the rate of heat transfer as follows: a). For using the 10 holes briquettes, the heat transfer rate is about 8.51 watts, b). In the burning of 12 holes briquettes, the resulting heat transfer rate is about 16.57 watts, c). While on the 14 holes briquettes burning, the rate of heat transfer is about 20.43 watts. When heat energy is applied to boil 5 liters of water, with a 10-hole briquette, the water boils within 23.54 minutes. When using 12 holes briquettes, the water boils in 21.31 minutes, and in the use of 14 holes briquettes, the water boils in 20.21 minutes. It is concluded that the shortest time to boil 5 liters of water is when using briquettes with 14 holes, which boils in 23.34 minutes. These results indicate that forced convection can speed up the briquette burning process and produce a fairly high temperature.